Anti-factor H antibody and its role in atypical hemolytic uremic syndrome - Raina, Rupesh; Mangat, Guneive; Hong, Gordon; Shah, Raghav; Nair, Nikhil; Abboud, Brian; Bagga, Sumedha; Sethi, Sidharth Kumar (Frontiers in Immunology, 2022)
Atypical hemolytic uremic syndrome (aHUS) an important form of a thrombotic microangiopathy (TMA) that can frequently lead to acute kidney injury (AKI). An important subset of aHUS is the anti-factor H associated aHUS. This variant of aHUS can occur due to deletion of the complement factor H genes, CFHR1 and CFHR3, along with the presence of anti-factor H antibodies. However, it is a point of interest to note that not all patients with anti-factor H associated aHUS have a CFHR1/R3 deletion. Factor-H has a vital role in the regulation of the complement system, specifically the alternate pathway. Therefore, dysregulation of the complement system can lead to inflammatory or autoimmune diseases. Patients with this disease respond well to treatment with plasma exchange therapy along with Eculizumab and immunosuppressant therapy. Anti-factor H antibody associated aHUS has a certain genetic predilection therefore there is focus on further advancements in the diagnosis and management of this disease. In this article we discuss the baseline characteristics of patients with anti-factor H associated aHUS, their triggers, various treatment modalities and future perspectives.